AF1q Contributes to Adriamycin-Induced Podocyte Injury by Activating Wnt/β-Catenin Signaling - Hongbo Zhang; Rui Ren; Juan Du; Tingli Sun; Ping Wang; Ping Kang (Karger Publishers, 2017)
Background/Aims: Injury of podocytes plays an important role in decline of glomerular filtration and proteinuria. It is well-known that proteinuria is associated with numerous chronic kidney diseases (CKD). However, the underlying mechanism of podocyte injury remains unclear. Methods: We used reverse transcription-quantitative PCR (RT-qPCR) to compare the expression level of the ALL1-fused from the chromosome 1q (AF1q) gene in mice and mouse podocytes (MPC5) with or without Adriamycin (ADR) treatment. The effects of AF1q on Wnt/ β-catenin signaling were investigated by determining the expressions of desmin, snail, WT1, nephrin and E-cadherin using western blotting. Results: We found that AF1q expression was elevated in podocytes treated with ADR than untreated cells. AF1q overexpression directly led to podocytes injury with increased levels of desmin and snail. Luciferase activity of TOPflash reporter was significantly increased in cells with AF1q overexpression than wild type cells whereas deletion of T-cell-factor-7 (TCF7) eliminated this effect. Immunoprecipitation assay evidenced that AF1q interacted with TCF7 and promoted both transcriptional and translational expressions of TCF7. Overexpression of AF1q increased protein expression of β-catenin. However, in podocytes with deletion of TCF7, AF1q was not able to promote β-catenin expression. Conclusion: Our findings demonstrated that aberrant expression of AF1q may activate Wnt/β-catenin signaling and result in podocyte injury.